Comparative analysis of main bio‐active components in the herb pair Danshen‐Honghua and its single herbs by ultra‐high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry. Issue 17 (31st July 2017) - Qu, Cheng; Pu, Zong‐Jin; Zhou, Gui‐Sheng; Wang, Jun; Zhu, Zhen‐Hua; Yue, Shi‐Jun; Li, Jian‐Ping; Shang, Li‐Li; Tang, Yu‐Ping; Shi, Xu‐Qin; Liu, Pei; Guo, Jian‐Ming; et al.
Abstract: A sensitive, reliable, and powerful ultra‐high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry method was developed for simultaneous quantification of the 15 main bio‐active components including phenolic acids and flavonoids within 13 min for the first time. The proposed method was first reported and validated by good linearity ( r 2 > 0.9975), limit of detection (1.12–7.01 ng/mL), limit of quantification (3.73–23.37 ng/mL), intra‐ and inter‐day precisions (RSD ≤ 1.92%, RSD ≤ 2.45%), stability (RSD ≤ 5.63%), repeatability (RSD ≤ 4.34%), recovery (96.84–102.12%), and matrix effects (0.92–1.02). The established analytical methodology was successfully applied to comparative analysis of main bio‐active components in the herb pair Danshen‐Honghua and its single herbs. Compared to the single herb, the content of most flavonoid glycosides was remarkably increased in their herb pair, and main phenolic acids were decreased, conversely. The content changes of the main components in the herb pair supported the synergistic effects on promoting blood circulation and removing blood stasis. The results provide a scientific basis and reference for the quality control of Danshen‐Honghua herb pair and the drug interactions based on variation of bio‐active components in herb pairs.